Modeling Priority Maintenance Cost Based on Top-Down and Bottom-Up Approach with Reconciliation of Forum Group Discussion - Mohammad Fauzan; Bambang Syairudin (Institut Teknologi Sepuluh Nopember, 2020)
PT XYZ engaged in the electricity industry, which has a strategic issue that’s reduction of BPP (Cost of Providing) electricity as one step in supporting the holding company policy. With the target of reduction BPP, where one component of the BPP is maintenance costs. This research shows the priority of maintenance costs of each Units that can be used in the drafting of the RKAP. In order to prioritize maintenance costs, it is necessary to compile an analysis of the cost, start from the proposed maintenance costs of each unit (using the bottom-up method) until evaluating cost from management (using the top-down method). This top-down method is strengthened by the analysis of priority maintenance costs from the expert's view using the Analytical Hierarchy Process (AHP) method with the Expert Choice V-11 Software tool. Then the results of prioritizing maintenance costs from the bottom-up and top-down methods are carried out reconciliation through Forum Group Discussion (FGD). Based on the results, that the highest weighting factor was Productivity (0.616), followed by Area (0.320), Specifications (0.064). Whereas the sub factor that is very dominant globally is having low production costs and the highest priority Unit for maintenance costs is Unit E.